PRELIMINARY EVIDENCE FOR A RELATIONSHIP BETWEEN HEART RATE VARIABILITY AND FATIGUE IN PATIENTS WITH INFLAMMATORY BOWEL DISEASE (IBD). (26th January 2023) - McGarva, Josie; Simons, Madison; Marchese, Sara; Tomasino, Kathryn; Pandit, Anjali; Hanauer, Stephen; Taft, Tiffany
Abstract: INTRODUCTION: Heart Rate Variability (HRV), the variation in time between each heartbeat, is a proxy for vagus nerve function and validated indicator of cardiovascular health. Lower HRV is associated with increased risk of cardiac events and greater vulnerability to psychological stress. Fatigue is a common, frustrating and persistent symptom for IBD patients, with multifaceted mechanisms including nutrient deficiencies, inflammation, and poor sleep. Lower HRV is associated with higher fatigue in patients with cancer and myalgic encephalomyelitis. We postulate lower HRV could be associated with fatigue in IBD patients. METHODS: Adults recruited from an outpatient IBD clinic wore a FitBit Inspire 2.0 for 14 days to monitor nighttime total time asleep, restlessness (# of ~30 second awakenings), and HRV (RMSSD in milliseconds (ms)). At baseline, weeks 1 and 2, participants completed the IBD Fatigue Scale and Harvey Bradshaw Index (HBI) or Simple Colitis Clinical Activity Index (SCCAI). Baseline laboratory testing for c-reactive protein (CRP), vitamins B12 and D, and ferritin was done. Averages for HRV and sleep metrics were computed for the 14-day period. Pearson's correlations assessed relationships between all study variables (any p < .10). Then, partial correlations calculated the relationship between HRV and fatigue scores while controlling for identified confounding variables. We report an interim analysis. RESULTS: 41 participants (63% female, 72.5% White, 92.7% non-Hispanic, 61% Crohn's, 40.02 (SD=14.18) yrs old). Most (>75%) were in remission (HBI/SCCAI< 4). 34% had B12< 400 pg/mL, 20% vitamin D< 30 ng/mL, 54% ferritin< 50 ng/mL. Participants slept an average of 6.6 hours with 24.1(5.48) awakenings per night. All reported fatigue, with 43.9% having severe levels. Fatigue severity and impact remained consistent over the study (p=.106). Average HRV was 31.79(19.0) ms (Range: 11 - 92). Older patients had lower HRV (r= -0.34, p=.025) with no gender differences. Patients who reported more fatigue had higher CRP (r= 0.29), more active IBD symptoms (r= 0.62), and spent more time asleep (r= 0.20). When controlling for these variables and age, IBD patients with lower HRV reported significantly more global fatigue (r= -0.38, p=.041). The relationship between HRV and fatigue was larger for lower HRV and fatigue impact (r= -0.37, p=.047) than fatigue severity (r= -0.30, p=.11). No relationships existed for restlessness, vitamins B12 or D, or ferritin and fatigue. CONCLUSIONS: When controlling for other contributors, patients with IBD and lower HRV reported more significant global fatigue and impact of fatigue on daily functioning. Findings may suggest lower HRV increases physical feelings of fatigue and reduces ability to manage fatigue impacts. Increasing HRV, e.g., with biofeedback training, may be a way to improve fatigue symptoms and management in IBD.